Safe and Efficient Electrical Installation For Residential Houses - Laela Worotikan; Rehan .O Barens; Dirly .G Tombokan; Christian Ys Pondalos; Salwa Ay Suprapto (Publikasi Indonesia, 2025)
Safe and efficient electrical installation in residential buildings is essential to ensure occupant comfort and safety. Common problems include the use of inappropriate components, inaccurate load planning, and insufficient implementation of protection systems such as grounding and circuit breakers. This study aims to analyze the basic principles of residential electrical installation and provide practical guidance for safe and efficient application according to national standards. The research employs a literature review and technical documentation analysis from textbooks, journals, and articles related to residential electrical systems. Data were collected through documentation observation, component specification analysis, and simulation testing of the installation system. The results indicate that proper implementation of electrical installation principles can minimize the risk of short circuits, fires, and equipment damage while optimizing energy consumption. This study also provides step-by-step guidelines for residential electrical installation. The implications of this research include enhancing the understanding of technicians and residents regarding safe and efficient electrical practices and serving as a foundation for developing energy-efficient and well-protected electrical systems.